International consensus for the treatment of autoimmune pancreatitis - Okazaki, Kazuichi; Chari, Suresh T.; Frulloni, Luca; Lerch, Markus M.; Kamisawa, Terumi; Kawa, Shigeyuki; Kim, Myung-Hwan; Lévy, Philippe; Masamune, Atsushi; Webster, George; Shimosegawa, Tooru (Pancreatology : official journal of the International Association of Pancreatology (IAP) ... [et al.], 2017)
The International Consensus Diagnostic Criteria (ICDC) for AIP has proposed two distinctive type of AIP, type 1 and type 2, and enabled us first to differentiate two types of AIP each other. By initial steroid treatment for induction of remission, remission can be successfully induced in almost all subjects with type 1 and type 2 AIP. As relapse rate in type 1 AIP is significantly higher than in type 2 AIP, there has been ongoing debate on how to treat effectively relapse of type 1 AIP. By a modified Delphi approach, a panel of international experts has proposed an international consensus on the treatment of AIP after intense discussion and deliberation during an international consensus symposium of the International Association of Pancreatology (IAP) 2016. Individual statements for nine clinical questions with recommendation levels and the therapeutic strategy have been proposed. The recommendations are based on the available evidence, and eastern and western experts' opinions to find standard treatment of AIP worldwide. These recommendations can be tailored according to the local expertise and context in the management of individual patients.